Researched methods for simplifying and optimizing particles for portable gaming devices - Shulha, M.; Matvieiev, D.; Nazarov, O.; Nazarova, N. (ХНУРЕ, 2023)
The object of the research is particle simulation systems and their modules. The aim of the work is to conduct a study of the performance of particle simulation systems and the optimization process to improve it. The methods of development and design are the analysis of the problem area of research, the choice of a particle simulation system based on their comparison for further study and optimization. As a result of work, a game simulation project was developed to demonstrate the effectiveness of the proposed ptimization methods. Об’єктом дослідження є системи симуляції часток та їх модулі. Метою роботи є проведення дослідження продуктивності систем симуляції часток та процес оптимізації для її покращення. Методами розробки та проектування є аналіз проблемної області дослідження, вибір системи симуляції часток на основі їх порівняння для подальшого вивчення та оптимізації. У результаті роботи було розроблено ігровий проект-симуляцію для демонстрації ефективності запропонованих методів оптимізації.
Keywords: vertices; simulation; particles systems; shaders; instructions count; unreal engine; вертекси; симуляція; системи часток; шейдери